2015
DOI: 10.1177/1356766715604661
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping – Predispositions, activations and applications in cross-cultural service interactions

Abstract: The aim of the article was to explore for stereotyping patterns in crosscultural service interactions. This research was set within the context of luxury hotel in Malaysia, where most of the service providers are non-Western. In-depth interviews and written diaries were used to develop deep narratives for the patterns of stereotyping adopted by the service providers. Predispositions, activations and applications of stereotypes were examined considering implicit theory and power distance. Associations between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…(#R2)This result supports findings, suggesting that traditional training programs may fail to overcome negative stereotypical beliefs (Barker and Härtel, 2004) and often produce negative reactions. As Cheok et al (2016) suggest, specific education can raise the awareness of implications of negative stereotyping that could be replaced by positive stereotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(#R2)This result supports findings, suggesting that traditional training programs may fail to overcome negative stereotypical beliefs (Barker and Härtel, 2004) and often produce negative reactions. As Cheok et al (2016) suggest, specific education can raise the awareness of implications of negative stereotyping that could be replaced by positive stereotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Research findings in intercultural hospitality research emphasize the importance of training programs for front-line staff (Cheok et al, 2016; Sizoo et al, 2005). Training can reinforce intercultural experience, and if employees are aware of the verbal and non-verbal codes used in different cultural areas, they are able to vary their verbal and non-verbal communication, in order to adapt to the type and scope of the encounter.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…En su estudio sobre los modales suecos, Beijering (2017: 53) (58) Additional participants could have been sought, but our analysis suggested that findings were converging and that little variation would be achieved with additional data (Conclusión; Cheok et al 2016).…”
Section: Inferencialidadmentioning
confidence: 99%